A haplotype at intron 8 of PTPRT gene is associated with resistance to Brucella infection in Argentinian creole goats - Rossi, Ursula; Hasenauer, Flavia Carolina; Caffaro, María Eugenia; Neumann, Roberto Daniel; Salatin, Antonio Omar; Poli, Mario Andres; Rossetti, Carlos Alberto (2018)
Brucellosis is the leading zoonosis on a worldwide scale and constitutes a major public health threat in many regions of the world. Several molecular markers associated with natural resistance to intracellular bacterial infection have been identified. Recently seven single-nucleotide polymorphisms (SNPs) located in the PTPRT gene were associated with resistance to Mycobacterium bovis infection in cattle. Here, we perform a case-control study to test if polymorphisms at PTPRT intron 8 might influence the resistance or susceptibility to Brucella infection in goats. DNA samples from 22 seropositive (cases) and 22 seronegative (controls) for brucellosis, unrelated female creole goats, were included in the present study. Four previously reported polymorphisms (SNP1: rs643551276, SNP2: rs651618967, SNP3: rs662137815 and SNP4: rs657542977) and a new SNP (SNP5: chr13: 691695526) were detected by PCR-DNA sequencing method. Genotypic and allelic frequencies differed significantly between cases and controls at SNPs 1, 2, 4 and 5 (p ≤0.001). Indeed, the SNP1 TT, SNP2 TT, SNP4 CC and SNP5 TT genotypes were associated with absence of Brucella-specific antibodies (ORs =0.019 to 0.045). Moreover, haplotype association analysis revealed a significant association of the TTCCT haplotype with protection to Brucella infection (p ≤1 × 10−4; OR =18), including the major allelic variants associated with resistance. These results represent the first evidence of genetic association between polymorphisms in the PTPRT gene and absence of brucellosis in goats.